Design optimization and robotic fabrication of tensile mesh structures: The development and simulation of a custom-made end-effector tool. (December 2016) - Kontovourkis, Odysseas; Tryfonos, George
This article presents an ongoing research, aiming to introduce a fabrication procedure for the development of tensile mesh systems. The purpose of current methodology is to establish an integrated approach that combines digital form-finding and robotic manufacturing processes by extracting data and information derived through elastic material behavior for physical implementation. This aspires to extend the capacity of robotically driven mechanisms to the fabrication of complex tensile structures and, at the same time, to reduce the defects that might occur due to the deformation of the elastic material. In this article, emphasis is given to the development of a custom-made end-effector tool, which is responsible to add elastic threads and create connections in the form of nodes. Based on additive fabrication logic, this process suggests the development of physical prototypes through a design optimization and tool-path verification.